2020
DOI: 10.1007/s11207-019-1574-8
|View full text |Cite
|
Sign up to set email alerts
|

Peculiar Solar Sources and Geospace Disturbances on 20–26 August 2018

Abstract: On the approach to minimum of Solar Cycle 24, on 26 August 2018, an unexpectedly strong geomagnetic storm (GMS) suddenly occurred. Its D st index reached -174 nT, that is the third of the most intense storms during the cycle. The analysis showed that it was initiated by a two-step long filament eruption, which occurred on 20 August in the central sector of the solar disk. The eruptions were accompanied by two large-scale divergent ribbons and dimmings of a considerable size and were followed by relatively weak… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 38 publications
4
34
0
Order By: Relevance
“…Such doublet structures in the solar wind speed enhancement are often observed in corotating interaction regions in association with longitudinally elongated and complex coronal hole(s), as was also discussed in Abunin et al. (2020). We also note in Figure 2a that the cosmic‐ray density I 0 ( t ) starts decreasing after the MFR period.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Such doublet structures in the solar wind speed enhancement are often observed in corotating interaction regions in association with longitudinally elongated and complex coronal hole(s), as was also discussed in Abunin et al. (2020). We also note in Figure 2a that the cosmic‐ray density I 0 ( t ) starts decreasing after the MFR period.…”
Section: Discussionsupporting
confidence: 60%
“…Figure 2a also shows a significant variation of I 0 (t) around noon on 24 August when the disturbance is recorded in the solar wind parameters. We do not analyze this variation in this paper, but Abunin et al (2020) considered it as an indication of another ICME which they identified. Figure 2c shows magnitudes of  ( ) w t ξ and  ( ) w t ξ , the parallel and perpendicular components of the anisotropy in Equation 9, while Figure 2d displays |ξ w (t)| as a function of the pitch angle (θ) between ξ w (t) and the IMF.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An unexpected and unusual strong geomagnetic storm (G3 class storm accordingly to the NOAA Space Weather Prediction Center) occurred on August 25, 2018. The analysis performed by Abunin et al (2020) revealed that the storm was initiated by a two-step long filament eruption in the central sector of the solar disk on August 20. It was accompanied by two consecutive ICMEs of a rather small size and low speed and followed by the HSS.…”
Section: Description Of the Complex Interplanetary And Geomagnetic Comentioning
confidence: 99%
“…The selected disturbed period is the first one in which Santa Maria Digisonde data are available in all phases of the storm. The August 25, 2018 geomagnetic storm is considered very complex by several authors (Abunin et al., 2020; Astafyeva et al., 2020) since it was caused by two consecutive Interplanetary Earth‐directed Coronal Mass Ejections (ICMEs) and a followed High‐Speed Solar Wind Stream (HSS).…”
Section: Introductionmentioning
confidence: 99%